2016
DOI: 10.4103/1319-3767.195559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin-converting enzyme inhibitor, lisinopril on morphological and biochemical aspects of fibrotic liver regeneration

Abstract: Background/Aims:Hepatic fibrosis results in defective liver regeneration following partial hepatectomy. Angiotensin converting enzyme (ACE) inhibitors can enhance liver regeneration and are also involved in the reduction of hepatic fibrosis. The present study has been conducted to evaluate the potential effect of an ACE inhibitor, lisinopril, on the morphological and biochemical aspects of fibrotic liver regeneration.Materials and Methods:Eight-week old female Sprague Dawley rats were made fibrotic by intragas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Angiotensin converting enzyme (ACE) inhibitors are widely used for the treatment of hypertension, cardiac remodeling, and play a crucial role in the management of mortality and morbidity associated with myocardial infarction and heart failure (Donnarumma et al, 2016). Recently, ACE inhibitors have been reported to protect against wide range of diseases including liver fibrosis (Ambreen et al, 2016;Saber et al, 2018a), lung injury (Boskabadi et al, 2019), and brain injury (El-Shoura et al, 2018). Moreover, ACE inhibitors were previously investigated during hepatic IR (Freise et al, 2006;Casillas-Ramirez et al, 2008;Yirmibesoglu et al, 2011) without exploring the exact molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin converting enzyme (ACE) inhibitors are widely used for the treatment of hypertension, cardiac remodeling, and play a crucial role in the management of mortality and morbidity associated with myocardial infarction and heart failure (Donnarumma et al, 2016). Recently, ACE inhibitors have been reported to protect against wide range of diseases including liver fibrosis (Ambreen et al, 2016;Saber et al, 2018a), lung injury (Boskabadi et al, 2019), and brain injury (El-Shoura et al, 2018). Moreover, ACE inhibitors were previously investigated during hepatic IR (Freise et al, 2006;Casillas-Ramirez et al, 2008;Yirmibesoglu et al, 2011) without exploring the exact molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…22 Measuring serum ACE levels is one of them, showing promising results in early studies, although some paradoxical outcomes have also been reported recently. [16][17][18]23 The issue of non--invasive methods has increasingly attracted many researchers, and frequently new studies on the topic are added to the literature.…”
Section: Resultsmentioning
confidence: 99%
“…14,24,25 Lisinopril has shown no major histomorphological alterations in regenerating fibrotic liver tissues and has a beneficial effect on the regression of liver fibrosis. 16 These conflicting results may also be explained by the lack of consideration of the polymorphism of ACE gene in the study population. Polymorphism of the ACE gene has the greatest impact on serum ACE levels with a strong genetic influence and large interindividual differences.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…In human, there is no evidence of the relationship of these drugs with liver regeneration, but in animals Ramalho et al describe that the losartan treatment diminished the activated stellate cell population, which is also known to participate in the liver fibrosis process 34 . On the other hand, Ambreen et al concluded that ACE inhibitor, lisinopril, did not produce major histo‐morphological alterations in regenerating fibrotic livers 48 h following partial hepatectomy in a rat model with the exception of non‐significant mitosis inhibition and increased hepatocyte binucleation 35 . However, it may improve the hepatic functional capability of fibrotic rats after surgery.…”
Section: Discussionmentioning
confidence: 99%